Single-Fluorescent Protein Reporters Allow Parallel Quantification of Natural Killer Cell-Mediated Granzyme and Caspase Activities in Single Target Cells - Liesche, Clarissa; Sauer, Patricia; Prager, Isabel; Urlaub, Doris; Claus, Maren; Eils, Roland; Beaudouin, Joël; Watzl, Carsten (Frontiers in Immunology, 2018)
Natural killer (NK) cells eliminate infected and tumorigenic cells through delivery of granzymes via perforin pores or by activation of caspases via death receptors. In order to understand how NK cells combine different cell death mechanisms it is important to quantify target cell responses on a single cell level. However, currently existing reporters do not allow the measurement of several protease activities inside the same cell. Here we present a strategy for the comparison of two different proteases at a time inside individual target cells upon engagement by NK cells. We developed single-fluorescent protein reporters containing the RIEAD or the VGPD cleavage site for the measurement of granzyme B activity. We show that these two granzyme B reporters can be applied in combination with caspase-8 or caspase-3 reporters. While we did not find that caspase-8 was activated by granzyme B, our method revealed that caspase-3 activity follows granzyme B activity with a delay of about 6 minutes. Finally, we illustrate the comparison of several different reporters for granzyme A, M, K and H. The approach presented here is a valuable means for the investigation of the temporal evolution of cell death mediated by cytotoxic lymphocytes.